Statistical Analysis and Forecasting of Indexes of Gender Asymmetry in the Labor Market of the Orenburg Region - L. V. Zolotova; L. V. Portnova (Статистика и экономика, 2023)
All-Russian and regional labor markets operate in an unstable socio-economic situation, which can contribute to the emergence of gender disproportion. The study of gender asymmetry is considered the most popular direction during periods of “economic upheaval”, since this kind of instability increases the inequality of men and women in various spheres of life. The state of turbulence in which the labor market of Russia as a whole and each of its regions is located contributes to the adaptation of each of its segments to new forms of work. This study examines the results of an analysis of the structure and trends in the dynamics of indexes of employment and unemployment of the male and female population in the Orenburg region for 2016-2021. The choice of the time period is justified by the uneven development of both the world and the Russian economy. Modern economic realities, in which the labor market exists, develops both in the country as a whole, and in its regions, experiencing a number of shocks, determine the scientific novelty of the issues under consideration.Purpose of the study. The main idea of the paper done is the possibility of using the methods of economic and statistical analysis to study dynamic differences in gender structures according to various characteristics, development directions that determine gender asymmetry in the labor market of the Orenburg region, and predict its main indexes for the medium term.Materials and methods. The information base of the study was the statistical information of Orenburgstat, which characterizes gender asymmetry in the labor market of the Orenburg region. To achieve this goal, a set of methods of economic and statistical analysis was applied, including the calculation of indexes of the structure and structural differences, dynamics, identifying trends, forecasting, as well as presenting the results of the study using tables and figures.Results. According to the results of the study, an average portrait of a busy and carefree person by gender was compiled. The characteristics of the male and female population in the labor market of the Orenburg region in 2021 compared to 2016 are highlighted. The study of structural differences was carried out according to the criterion of V. Ryabtsev, during which it was noted that there were no significant changes in the structures of employed men and women. A significant level of differences characterizes the age structure of unemployed men and women in 2021 compared to 2016, as well as the structure of unemployed men by level of education. The study made it possible to assert that in the dynamics of indexes characterizing gender inequality in the labor market of the Orenburg region, unstable changes are observed. The study tested the hypothesis of the presence/absence of trends in the time series of indexes characterizing gender asymmetry in the labor market of the region. For this purpose, one of the modifications of the series criterion was used. The assumption that there is no trend in the dynamics series under consideration has not been confirmed, therefore, the trend exists. Taking into account this circumstance, trend models were created, among which, according to the best statistical characteristics, second-order polynomial models were selected. With the help of the selected polynomials of the second degree, it was determined that in the dynamics of employment and unemployment indexes of the male and female population, downward trends of change prevail. Further, their prospective indexes were calculated. Conclusion. The study made it possible to analyze the main vectors that are emerging in the field of employment and unemployment in the regional labor market by gender, and to predict their main indexes for the medium term. In the dynamics of the number of both male and female labor force in the Orenburg region, unstable trends will be observed in the future. The number of women employed in the region’s economy will grow; the number of unemployed women will decrease. In the forecast period, the number of employed men in the economy of the Orenburg region will change under the influence of a downtrend. The number of unemployed men in the period from 2023 to 2025 will tend to decrease.